Synthesis and antimicrobial properties of apatite- related Cu, Zn-doped calcium phosphate - Grynyuk, I.I.; Strutynska, N.Yu.; Vasyliuk, O.M.; Prylutska, S.V.; Livitska, O.V.; Slobodyanik, M.S. (Reports of the National Academy of Sciences of Ukraine, 2021)
The nanoparticles (30-50 nm) of apatite-related calcium phosphates have been obtained by the coprecipitation method from an aqueous solution at molar ratios Са/Р = 1,67, CО32–/РО43–= 1 and (Cu2+, Zn2+) : Ca = 1 : 50 and a temperature of 25 0C. According to chemical analysis data, the prepared calcium phosphates contain cationic (Na+ (0.19-0.21 wt%),Cu2+ (0.42 wt%) and Zn2+ (0.36 wt%)) and anionic (C (0.98-1.02 wt%)) dopants. In the FTIR spectra of prepared calcium phosphates, the positions of vibration modes of carbonate groups confirmed the partial substitution of phosphate anion by carbonate group (B type) in the apatitetype structure. It was found that the doping of apatite-related calcium phosphates with Cu2+ and Zn2+ cations led to their increased inhibitory effect on gram-positive (Staphylococcus aureus) and gram-negative (Pseudomonas aeruginosa) microorganisms. Tenfold inhibition of S. aureus cell growth was observed at the addition of 5 mM of (Na+, Cu2+, Zn2+, CO32–)-containing calcium phosphate, while its noticeable effect on gram-negative bacteria (P. aeruginosa) was observed only at its amount of 10 mM. The obtained results indicate the prospects of using synthesized nanoparticles (Na+, Cu2+, Zn2+, CO32–)-containing calcium phosphate in the development of materials with antibacterial properties.